2019
DOI: 10.2478/s11756-019-00255-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic resources of relict populations of Pinus sylvestris (L.) in Western Carpathians assessed by chloroplast microsatellites

Abstract: The relict character of the Scots pine populations from the Tatra Mts. (Western Carpathians) was formed on scarcely accessible, ecologically extreme habitats, in areas which were not under human activity. An exhaustive genetic analysis of the Scots pine populations from the refugial locations in the Tatra Mts. (Poland) had not yet been. In this study, we characterize the genetic variation and differentiation of the relict Scots pine populations from the Tatra Mts., to provide information on their genetic resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The number and distribution of four repeats in the eight Ficus cp genomes, and the distribution of repeast were similar in the cp genomes of Ficus, which was strongly related to the high conserved in Ficus species. The cpSSR markers have been frequently used for intraspeci c identi cation and genetic evolutionary analysis because of their high mutation rate [40][41][42]. The results of this study indicated that the mono-nucleotide repeats were the richer repeat type in eight Ficus species, with the A/T as the enriched repeat motif, similar to other higher plant studies [13,43], indicating that the higher plants were dominated by low-level repeat motif [44].…”
Section: Identi Cation Of Ssrs and Repeat Sequencessupporting
confidence: 69%
“…The number and distribution of four repeats in the eight Ficus cp genomes, and the distribution of repeast were similar in the cp genomes of Ficus, which was strongly related to the high conserved in Ficus species. The cpSSR markers have been frequently used for intraspeci c identi cation and genetic evolutionary analysis because of their high mutation rate [40][41][42]. The results of this study indicated that the mono-nucleotide repeats were the richer repeat type in eight Ficus species, with the A/T as the enriched repeat motif, similar to other higher plant studies [13,43], indicating that the higher plants were dominated by low-level repeat motif [44].…”
Section: Identi Cation Of Ssrs and Repeat Sequencessupporting
confidence: 69%
“…Simple sequence repeats (SSRs or microsatellites) are very often used in population, ecological and conservation genetics as effective molecular markers mainly due to the high level of genetic polymorphism detected by them and wide distribution throughout the whole chloroplast genome [60][61][62][63]. Initially, isolation and characterization of microsatellite markers and the development of primers amplifying these regions was quite a laborious and expensive task.…”
Section: Genome Featuresmentioning
confidence: 99%
“…Simple sequence repeats (SSRs or microsatellites) are very often used in population, ecological and conservation genetics as effective molecular markers. Their most important advantages are the high level of genetic polymorphism detected by them and wide distribution throughout the genome of chloroplasts, as well as trouble-free amplification, fast electrophoretic separation or objective and simple statistical analysis [ 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%